Proficiency testing programs for Alzheimer's disease cerebrospinal fluid biomarkers. (August 2012) - Mattsson, Niklas; Andreasson, Ulf; Carrillo, Maria C; Persson, Staffan; Shaw, Leslie M; Zegers, Ingrid; Zetterberg, Henrik; Blennow, Kaj
Cerebrospinal fluid (CSF) biomarkers are increasingly used for diagnosis of Alzheimer's disease in research, clinical trials and clinical settings. As for other biochemical measurements, variability between laboratories for these biomarkers may be monitored by proficiency testing programs, where participating laboratories use their local routine methods to analyze test samples shipped from a central laboratory. In this review, we summarize the results from the last years' pilot proficiency programs and describe the ongoing standardization efforts in this area. Global proficiency testing for CSF biomarkers is now fully established. It will continue to play an important part in the standardization of measurements that is a prerequisite for the broad-scale future implementation of CSF biomarkers.